antioxidant capacity of ethanol extract of garlic (Allium sativum) in vitro - Amirna, Nina (PHARMACY UMI JOURNAL SYSTEM, 2024)
Garlic is one type of plant that is familiar in everyday life and has a very important function for human life. The purpose of this study was to determine the antioxidant capacity of the ethanol extract of garlic (allium sativum). This type of research was a laboratory experiment using the spectrophotometer method based on the calculation of the IC550 value of the extract at the value of y = 0.9983x + 16.763 (r = 9983) ; and IC550 value of 107.493 µg/mL. The results of this study illustrate that the ethanol extract of garlic has an antioxidant effect against DPPH free radicals.